ðŸ‘‰ Try now NerdPal! Our new math app on iOS and Android

# Exact Differential Equation Calculator

## Get detailed solutions to your math problems with our Exact Differential Equation step-by-step calculator. Practice your math skills and learn step by step with our math solver. Check out all of our online calculators here.

Go!
Symbolic mode
Text mode
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

###  Difficult Problems

1

Here, we show you a step-by-step solved example of exact differential equation. This solution was automatically generated by our smart calculator:

$\frac{dy}{dx}=\frac{5x^2}{4y}$
2

Rewrite the differential equation in the standard form $M(x,y)dx+N(x,y)dy=0$

$4ydy-5x^2dx=0$
3

The differential equation $4ydy-5x^2dx=0$ is exact, since it is written in the standard form $M(x,y)dx+N(x,y)dy=0$, where $M(x,y)$ and $N(x,y)$ are the partial derivatives of a two-variable function $f(x,y)$ and they satisfy the test for exactness: $\displaystyle\frac{\partial M}{\partial y}=\frac{\partial N}{\partial x}$. In other words, their second partial derivatives are equal. The general solution of the differential equation is of the form $f(x,y)=C$

$4ydy-5x^2dx=0$

Find the derivative of $M(x,y)$ with respect to $y$

$\frac{d}{dy}\left(-5x^2\right)$

The derivative of the constant function ($-5x^2$) is equal to zero

0

Find the derivative of $N(x,y)$ with respect to $x$

$\frac{d}{dx}\left(4y\right)$

The derivative of the constant function ($4y$) is equal to zero

0
4

Using the test for exactness, we check that the differential equation is exact

$0=0$

The integral of a function times a constant ($-5$) is equal to the constant times the integral of the function

$-5\int x^2dx$

Apply the power rule for integration, $\displaystyle\int x^n dx=\frac{x^{n+1}}{n+1}$, where $n$ represents a number or constant function, such as $2$

$-5\left(\frac{x^{3}}{3}\right)$

Multiplying the fraction by $-5$

$\frac{-5x^{3}}{3}$

Since $y$ is treated as a constant, we add a function of $y$ as constant of integration

$\frac{-5x^{3}}{3}+g(y)$
5

Integrate $M(x,y)$ with respect to $x$ to get

$\frac{-5x^{3}}{3}+g(y)$

The derivative of the constant function ($\frac{-5x^{3}}{3}$) is equal to zero

0

The derivative of $g(y)$ is $g'(y)$

$0+g'(y)$
6

Now take the partial derivative of $\frac{-5x^{3}}{3}$ with respect to $y$ to get

$0+g'(y)$

Simplify and isolate $g'(y)$

$4y=0+g$

$x+0=x$, where $x$ is any expression

$4y=g$

Rearrange the equation

$g=4y$
7

Set $4y$ and $0+g'(y)$ equal to each other and isolate $g'(y)$

$g'(y)=4y$

Integrate both sides with respect to $y$

$g=\int4ydy$

The integral of a function times a constant ($4$) is equal to the constant times the integral of the function

$g=4\int ydy$

Applying the power rule for integration, $\displaystyle\int x^n dx=\frac{x^{n+1}}{n+1}$, where $n$ represents a number or constant function, in this case $n=1$

$g=4\cdot \left(\frac{1}{2}\right)y^2$

Multiply the fraction and term in $4\cdot \left(\frac{1}{2}\right)y^2$

$g=\frac{4\cdot 1}{2}y^2$

Multiply $4$ times $1$

$g=\frac{4}{2}y^2$

Divide $4$ by $2$

$g=2y^2$
8

Find $g(y)$ integrating both sides

$g(y)=2y^2$
9

We have found our $f(x,y)$ and it equals

$f(x,y)=\frac{-5x^{3}}{3}+2y^2$
10

Then, the solution to the differential equation is

$\frac{-5x^{3}}{3}+2y^2=C_0$

Group the terms of the equation

$2y^2=C_0-\frac{-5x^{3}}{3}$

Multiplying the fraction by $-1$

$2y^2=C_0+\frac{5x^{3}}{3}$

Combine all terms into a single fraction with $3$ as common denominator

$2y^2=\frac{3\cdot C_0+5x^{3}}{3}$

We can rename $3\cdot C_0$ as other constant

$2y^2=\frac{C_1+5x^{3}}{3}$

Divide both sides of the equation by $2$

$y^2=\frac{C_1+5x^{3}}{6}$

Removing the variable's exponent

$\sqrt{y^2}=\pm \sqrt{\frac{C_1+5x^{3}}{6}}$

Cancel exponents $2$ and $1$

$y=\pm \sqrt{\frac{C_1+5x^{3}}{6}}$

As in the equation we have the sign $\pm$, this produces two identical equations that differ in the sign of the term $\sqrt{\frac{C_1+5x^{3}}{6}}$. We write and solve both equations, one taking the positive sign, and the other taking the negative sign

$y=\sqrt{\frac{C_1+5x^{3}}{6}},\:y=-\sqrt{\frac{C_1+5x^{3}}{6}}$

Combining all solutions, the $2$ solutions of the equation are

$y=\sqrt{\frac{C_1+5x^{3}}{6}},\:y=-\sqrt{\frac{C_1+5x^{3}}{6}}$
11

Find the explicit solution to the differential equation. We need to isolate the variable $y$

$y=\sqrt{\frac{C_1+5x^{3}}{6}},\:y=-\sqrt{\frac{C_1+5x^{3}}{6}}$

##  Final answer to the problem

$y=\sqrt{\frac{C_1+5x^{3}}{6}},\:y=-\sqrt{\frac{C_1+5x^{3}}{6}}$

### Are you struggling with math?

Access detailed step by step solutions to thousands of problems, growing every day!